PENINGKATAN KINERJA GURU MATEMATIKA DALAM PEMBELAJARAN MELALUI SUPERVISI KOLABORATIF DI SMP NEGERI 1 MERAWANG - Andriana (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2021)
This study intends to improve the performance of mathematic teachers in learning through collaborative academic supervision. This research had the form of School Action Research which was conducted in two cycles. Each cycles is taken place in four steps, namely planning, acting, observing, and reflecting. The action was taken place in two cycle meeting. Each meeting taken place the collaborative supervision stages, namely pre-observation, learning observation, post-observation, data analysis of supervision, providing feedback, and providing follow-up. The research data had the form of observations in the field and documentation. The instrument of the main data collection was observation and documentation. Data analysis was showed by using qualitative and quantitative tehnique. The result of each cycle showed an increase in the performance of mathematic teachers in learning. The increase was able to be seen from the average performance score of cycle I and cycle II. The average of teachers performance assesment was 68.00 in cycle I and it reached 88,89 in cycle II. Thus, it was able to conclude that collaborative supervision can improve the performance of Mathematic teachers in learning at SMP Negeri 1 Merawang.